Analytic-holistic thinking influence on information use during sensemaking - Lin, Mei Hua * (Sunway University College, 2009)
The present study looks at how cultural differences in cognition pose a challenge to the management of information. Analytic-Holistic (AH) thinking, in particular, appears to influence information selection, attribution, and ultimately, sensemaking. This study, conducted in the United States, used 47 Americans and 47 Malaysian students studying in the U.S. The participants completed the Holism Scale; read a scenario and responded to a recognition test and an attribution assessment, developed for this study. First, Malaysians were found to be higher than the Americans in a scale of holistic thinking. Second, they also remembered more situational information. Thirdly, no differences were found between the two groups in situational attribution. Finally, proposed mediations with recognition of information as a mediator of AH thinking and Attribution were not significant. Differences in cognition affected types of information remembered. Implications of results on information management, sensemaking, and barriers to multinational teamwork are discussed.